2009
DOI: 10.1016/j.actao.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Can salvage logging affect seed dispersal by birds into burned forests?

Abstract: The recovery of vegetation in Mediterranean ecosystems after wildfire is mostly a result of direct regeneration, since the same species existing before the fire regenerate on-site by seeding or resprouting. However, the possibility of plant colonization by dispersal of seeds from unburned areas remains poorly studied. We addressed the role of the frugivorous, bird-dependent seed dispersal (seed rain) of fleshy-fruited plants in a burned and managed forest in the second winter after a fire, before on-site fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Furthermore salvage harvesting can produce ground disturbance affecting vegetation development (Macdonald, 2007). The presence of patches of standing dead trees could moreover favour tree recruitment by providing perching sites for frugivore birds, potentially improving species richness in the regeneration layer (McClanahan and Wolfe, 1993;Rost et al, 2009;Castro et al, 2009). Ground cover conditions contributed to patterns of seedling occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore salvage harvesting can produce ground disturbance affecting vegetation development (Macdonald, 2007). The presence of patches of standing dead trees could moreover favour tree recruitment by providing perching sites for frugivore birds, potentially improving species richness in the regeneration layer (McClanahan and Wolfe, 1993;Rost et al, 2009;Castro et al, 2009). Ground cover conditions contributed to patterns of seedling occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Different post-fire treatments altered jay behavior in terms of seed dispersal, which subsequently altered the spatial pattern of seedling recruitment. Recent studies are showing that salvage logging alters other interactions as well, such as herbivory (increasing its impact after log removal; Relva et al 2009), ungulatewolf interaction (Hebblewhite et al 2009), or seed dispersal by frugivorous birds (Rost et al 2009(Rost et al , 2010. All this supports that salvage logging may interfere with a wide array of species interactions, adding to the growing body of evidence that shows its potential impact at the ecosystem level.…”
Section: Discussionmentioning
confidence: 83%
“…By contrast, salvage logging reduced the natural recruitment of new oaks, as it created a habitat not used by the main seed disperser (Castro et al 2010a). Furthermore, it is likely that the conditions of our experimental salvage logging even produced an over-estimation of the role of jays in the salvage logging treatment, as the permanence of trunk piles could have increased the use of this habitat for caching (see Rost et al 2009Rost et al , 2010 for a similar pattern for frugivorous, bird-dependent seed dispersal). In addition, seedling recruitment in the salvaged areas is largely dependent on the presence of live trees that survived the fire (either isolated or in small clusters), as those trees were highly attractive to jays.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have reported that bird-dependent seed rain strongly relies on habitat structures that act as dispersal foci, such as isolated trees that act as perches (Guevara & Laborde, 1993;Pausas et al 2006, Herrera & García 2009). After logging, wood debris piles and barriers built in a burned pine forest can also act as dispersal foci (Rost et al 2009). Thus, the variability of postfire treatments after logging, which leads to the presence of different microhabitats on a small scale, may have important implications for bird-dependent seed rain, depending on the differential use that seed dispersers make of the resulting microhabitats.…”
mentioning
confidence: 99%